Relevansi Pendidikan Multikultural pada Hakikat dan Tugas Peserta Didik Dalam Perspektif Hadis - Maslani, Maslani; Maulana, Ahmad Nanda; Ramadhan, Fatih Nur Afif; Aliyah, Hani Rolis (CV. Rayyan Dwi Bharata, 2025)
This article discusses the relevance of multicultural education in understanding the nature and duties of students based on the perspective of the hadith. This research is motivated by the challenges of student character in the modern era, which tends to be individualistic and lacks respect for diversity. Through a qualitative approach with literature study, this article examines the multicultural values contained in the hadith of the Prophet Muhammad SAW, such as tolerance, justice, and respect for cultural, religious, and ethnic differences. The results of the study indicate that multicultural education is aligned with Islamic values, especially in shaping the character of students who are tolerant, open, and have noble morals. The values in the hadith strengthen the understanding that students are unique and diverse learning subjects, who need to be facilitated to develop holistically. Thus, the integration of multicultural values in education is crucial to creating a harmonious and inclusive learning environment in a pluralistic society.